Role of Tourism in Poverty Alleviation. - Roy, Hiranmoy (2011)
The objective of the paper is to study the role of tourism in poverty alleviation. The problem of poverty is a fundamental problem and tourism is one of the many important ways to solve this. The scope lies in the fact that tourism may generate income which is supposed to alleviate poverty. This may create a tourism-income-poverty reduction spiral. We propose to answer the question: Is there a strong association between tourism and poverty reduction? I have followed the methodology to study existing literature on tourism and examined the relationship between tourism, poverty and per capita income and applied the multiple regressions for panel data to study the relationship. Findings of the study are that in India tourism could not make a dent in the problem of poverty as revealed in the study, which is contrary to the empirical evidence for some other developing countries..